(untitled) (Хабаршы. Психология және социология сериясы, 2015)
Firstly, public authorities, namely the local executive power should be more demanding of employers, despite the fact that they are foreign in vestors. They must be aware of the need for systematic social policy, both within the organization and outside it. We agree with the official statistics that businesses take on social obligations, but at the same time providing a onetime aid does not cover and does not compare to the damage they cause to the environment in the region, which shows the industry.Second, the results of quantitative surveys and interviews showed that those means which the employer directs the purchase of equipment is not enough. In this connection, the government should be able, through the institution of bilateral, trilateral commission to conduct specialized inspection equipment in industrial plants.Third, the number of employees in enterprises is huge, working in different departments of the company, they notice that the socio psychological climate in the team, one of the important aspects of working life, in connection with which both the employer and the public authorities should pay attention to the improvement, above all, a social enterprise im age. Fourth, high staff turnover, the desire to change their place of work, show that industrial jobs associated with a high level of risk and danger. In this connection, it is necessary to work with the staff of the permanent ob servance of safety rules. However, differentiated pay, social and economic difficulties of the workers, spurring him to break the rules, in connection with what are related accidents in the workplace. Consequently, systematic work with the staff, daily check on the working place of work, training may improve the situation by reducing the number of occupational injuries. Fifth, the trade unions as organizations defending the interests of workers need to be aware of everything that happens in the departments. More common workers, not with trade union activists. Because workers perceive them selves as a protest organized enough power and if you have any conflicts with management companies, to keep from strikes, interruption fail.